The Impact of Syncope On Hip Fracture Incidence Among the Elderly: A Cross-Sectional Study - Wijdan Abbas Eneama; Issa, Wafaa Abdulkadhim; Salah Naser (Universitas Muhammadiyah Sidoarjo, 2025)
Syncope is defined as a transient loss of consciousness resulting from a temporary reduction in cerebral blood flow, followed by spontaneous recovery. This study aimed to investigate the prevalence of syncope episodes among elderly individuals presenting with hip fractures. An observational cross-sectional study was conducted on 200 patients aged 45 years and above, from October to December 2024. The results indicated that 16% of patients who experienced syncope had sustained hip fractures, which is significantly higher than the estimated 10–12% hip fracture rate in the general elderly population according to recent global data [1]. Notably, 70% of mild fractures were associated with brief syncope episodes lasting less than one minute, implying partial retention of protective reflexes during the fall. The overall fracture rate among syncope patients reached 36%, comprising 16% hip fractures and 20% other types (e.g., wrist, ankle). Middle-aged females (aged 45–50 years) with comorbidities such as balance disorders, hypertension, or diabetes emerged as a particularly vulnerable group. These individuals should be prioritized in fall-prevention interventions to mitigate injury risks associated with syncope. Highlights: Hip fractures occurred in 16% of elderly syncope patients, higher than global estimates for the general elderly population. Syncope lasting more than 2 minutes, absence of warning signs, and recurrent episodes were strongly linked to severe fractures. Middle-aged women with comorbidities (hypertension, diabetes, balance disorders) were identified as the most vulnerable group.